Licensing of financial investment companies by the Central Bank - جاسم رسل جعفر; أمين خالص نافع (Journal of Legal Sciences, 2021)
Financial investment companies are a form of image of companies contributing under Iraqi law. All legal provisions of joint stock companies are applied to financial investment companies. In view of the specificity of the activity of the financial investment companies, represented mainly by the formation and management of the securities in the stock market, and the consequent entry into contractual agreements with investors and deposit their funds to be employed and invested in the field of securities, and in order to protect the funds of investors deposited with companies, To ensure that these companies carry out the activities specified for them by law, Iraqi law requires that these companies obtain a license issued by the Central Bank in accordance with the legal regulations. The Central Bank of Iraq being the sectoral body responsible for regulating and controlling the work of financial investment companies to study and evaluate all securities submitted by the company, and the Central Bank follows the procedures prescribed by law.